When the world ends: Study of #fakewesteros twitter fan community during the final season of game of thrones. Issue 1 (18th October 2019) - Forcier, Eric
ABSTRACT: #FakeWesteros is an online fan community that originated on Twitter when the worldwide blockbuster television series Game of Thrones (GoT) aired its first season in 2011. Fans from around the world live‐tweeted episodes as a role‐playing activity, assuming the identity of a character from the series in their tweets. This poster will present an analysis of this practice during the 2019 airing of the final season of GoT . Preliminary results reveal how fans responded to the controversial last episodes, demonstrating how Twitter was used to express their thoughts and feelings regarding the characters, the narrative and its creators. Findings indicate how this innovative use of the digital space represents evolving forms of information sharing. Findings inform ongoing research into the information‐based practices of fans and provides new insights into the evolution of online communities, particularly how loyalty to a shared identity can extend bonds beyond fandom.